Success purpose tendencies of high school students Lise öğrencilerinin başarı amaç yönelimleri - Kösterioğlu, İlker and Çelen, Ümit and Akın Kösterioğlu, Meltem and Ahıska, Rasim (Journal of Human Sciences, 2019)
The aim of this research is to investigate success purpose tendencies of high school students related to the high school type variable. The data was obtained through a developed questionaire for 796 students attending different high schools in Amasya and 2x2 Achievement Goals Questionnaires. For the analyses of the data t-test, one-way variance analysis and (LSD) test to determine the differerence among the groups in the variance analysis and ki-square test were used. Furthermore, descriptive statistical scores that the students got from the scale were presented. When the averages investigated, it is seen that learning approach sub-scale average scores are the highest and performance avoidance average scores are the lowest. It is found out that female students have higher average scores related to learning approach and learning avoidance sub-scale whereas the male students have higher average scores in performance approach and performance avoidance sub-scale. There has seen no difference in the class level success purpose tendency average scores of the students related to the class levels. When the scores of the students related to the high school type investigated, there has seen no difference in the learning avoidance sub-scale average scores regarding to the type of school. However, there is a statistically difference in the average scores of the other sub-scale. There is a meaningful relationship between the success perception of the students and success purpose tendency sub-scale in which the students got the highest scores. The adoption in the the percentage of learning approach tendency of the students who accept themselves partially successful is higher than the percentage of learning approach tendency of the students who see themselves partially unsuccessful.The adoption in the the percentage of learning avoidance and performance avoidance tendency of the students who accept themselves partially unsuccessful is higher than the percentage of the performance approach tendency of the students who see themselves unsuccessful. Extended English summary is in the end of Full Text PDF (TURKISH) file. Özet Bu araştırmanın amacı öğrencilerin başarı amaç yönelimlerini lise türü değişkeni açısından incelemektir. Veriler Amasya ilindeki farklı liselerde öğrenim gören 796 öğrenciden geliştirilen anket formu ve 2x2 Başarı Amaç Yönelimi Ölçeği aracılığıyla toplanmıştır. Verilerin analizinde t-testi, tek yönlü varyans analizi ve varyans analizinde farklı bulunan grupların tespiti için asgari önemli fark (LSD) testi ve ki-kare testi kullanılmıştır. Ayrıca öğrencilerin ölçekten aldıkları puanların tanımlayıcı istatistikleri sunulmuştur. Ortalamalar incelendiğinde öğrenme yaklaşma alt ölçeği puan ortalamasının en yüksek, performans kaçınma alt ölçeği puan ortalamasının ise en düşük olduğu saptanmıştır. Öğrenme yaklaşma ve öğrenme kaçınma alt ölçeklerinde kızların, performans yaklaşma ve performans kaçınma alt ölçeklerinde ise erkeklerin puan ortalaması daha yüksek olduğu belirlenmiştir. Öğrencilerin sınıf düzeyleri başarı amaç yönelimi puan ortalamaları sınıf düzeyine göre farklılık elde edilmemiştir. Öğrencilerin lise türüne göre puanları incelendiğinde öğrenme kaçınma alt ölçeği puan ortalamalarının lise türüne göre farklılık göstermediği; diğer alt ölçek puan ortalamalarında ise istatistiksel olarak anlamlı şekilde farklılık bulunduğu belirlenmiştir. Öğrencilerin başarı algılarıyla en yüksek puan aldıkları başarı amaç yönelimi alt ölçeği arasında istatistiksel olarak anlamlı bir ilişki olduğu saptanmıştır. Kendini kısmen başarılı ve başarılı gören öğrencilerin öğrenme yaklaşma yönelimini benimseme yüzdesi kısmen başarısız ve başarısız görenlerden fazladır. Kısmen başarısız öğrencilerde öğrenme kaçınma ve performans kaçınma yönelimini benimseme yüzdesi, başarısız gören öğrencilerde ise performans yaklaşma yönelimini benimseyen öğrenci yüzdesi diğerlerinden fazladır.